(3fXQjI GdefXeI (B:s (3eONd GdYedjGJ (B/s - (3efUhQ, WGgQ eMSfs; (3GdNaGLj, fYeI YHGS s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2010)
(3GdJMOjGJ GdJj JhGLg GdefXeGJ aj GdbQf GdMGOj h GdYTQjf , GdbjGOI h Jahb GdefXeGJ ` GdJZjjQ GdJfWjej , GdJWhjQ GdJfXjej , GdGHOGY h GdJYde GdJfXjej , eY hLhO CSFdIYGeI , CSFdI acQjI h CSFdI NjGQGJ eJYOOI(B.s
(3eQGLY U(B.225s
Keywords: (3EOGQI GdCYeGds; (3GdEOGQIs; (3GdbjGOIs; (3GdefXeGJs